Measuring the role of conditioning and stimulus generalisation in common fears and worries - Haddad, ADM; Xu, M; Raeder, S; Lau, J (2013)
Common and persistent fears may emerge through learning mechanisms such as fear conditioning and generalisation. Although there have been extensive studies of these learning processes in healthy but also psychiatric samples, many of the tasks used to produce conditioning and assess generalisation either use painful and aversive stimuli as the unconditioned stimuli (UCS), or suffer from poor belongingness between the conditioned stimuli and the UCS. Here, we present novel data from a paradigm designed to examine fear conditioning and generalisation in healthy individuals. Two female faces served as conditioned threat cue (CS+) and conditioned safety cue (CS-) respectively. The CS+ was paired repeatedly with a fearful, screaming face (unconditioned stimulus). Generalisation included intermediate faces which varied in their similarity to the CS+ and CS-. We measured eyeblink startle reflex and self-reported ratings. Acquired fear of the CS+ generalised to intermediate stimuli in proportion to their perceptual similarity to the CS+. Our findings demonstrate how fears of new individuals may develop based on resemblance to others with whom an individual has had negative experiences. The paradigm offers new opportunities for probing the role of generalisation in the emergence of common and persistent fears. © 2013 Copyright Taylor and Francis Group, LLC.